Olive Oil in the North-West of Tunisia Findings from a Value Chain and Jobs Survey - Weber, Michael (World Bank E-Library Archive, 2020)
This report describes the findings of the survey on olive oil value chain in the North West of Tunisia, focusing particularly on the current and potential jobs landscapes. The survey also benchmarks the performance of the value chain against other leading countries in olive oil industry to determine potential productivity gaps and areas for improvements to ultimately increase the sectors' competitiveness and create more and better jobs. Together with the companion report on olive oil market segmentation, it provides insights on potential areas for policy interventions. This study is part of the "Value Chain Development for Jobs in Lagging Regions - Let's Work Program in Tunisia" which aims to identify some of the most binding constraints affecting the creation and productivity of jobs within targeted value chains in a lagging region in Tunisia and inform relevant World Bank Group lending projects currently in preparation to help tackle these constraints